2000
DOI: 10.1139/w99-128
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of MS-2 phage and poliovirus in groundwater

Abstract: Since temperature affects the inactivation rate of viruses in natural water systems, the aim of this study was to determine if a temperature shift could influence the structural integrity of model viruses. When crude lysates of MS-2 phage were seeded into groundwater microcosms and incubated at 27 degrees C, complete virus inactivation took place in eight days. The temperature was then shifted to 4 degrees C. Three days after the temperature shift, a two-log increase in virus titer (reactivation) occurred. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…For example, Ottosson and Stenström [29] found that MS2 had a significantly higher decay rate in the tyndallized sediments than in the non-tyndallized sediments. Alvarez et al [28] got similar results for virus in groundwater, showing that inactivation of MS2 and poliovirus in the groundwater filtered through a 0.2-m pore filter was slightly faster than in raw groundwater. However, Nasser et al [58] and Davies et al [59] reported more rapid inactivation of MS2 and PRD1 in nonsterilized as compared to sterilized soils.…”
Section: Virus Adsorption Onto the Red Soil-equilibrium Studymentioning
confidence: 73%
See 1 more Smart Citation
“…For example, Ottosson and Stenström [29] found that MS2 had a significantly higher decay rate in the tyndallized sediments than in the non-tyndallized sediments. Alvarez et al [28] got similar results for virus in groundwater, showing that inactivation of MS2 and poliovirus in the groundwater filtered through a 0.2-m pore filter was slightly faster than in raw groundwater. However, Nasser et al [58] and Davies et al [59] reported more rapid inactivation of MS2 and PRD1 in nonsterilized as compared to sterilized soils.…”
Section: Virus Adsorption Onto the Red Soil-equilibrium Studymentioning
confidence: 73%
“…However, published results on the effect of autochthonous microorganisms on virus inactivation are generally not consistent [28][29][30]. Ferguson et al [31] reviewed that up to date, very few studies have examined the impact of such biological factors as antagonism, competition, and predation on inactivation/disintegration when evaluating transport of pathogens in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic composition as well as pH has been reported to be important factors that influence the kinetics of viral inactivation in a variety of systems. In addition, the presence of organic matter in water directly or indirectly contributes to viral stability or inactivation (Alvarez et al, 2000). Eubanks and Farrah (1981) reported that poliovirus and other enteroviruses in sodium fluoride solution were rapidly inactivated, whereas other sodium salt had little or no effect on virus infectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses have been shown to persist better in sewage-polluted water than in non-polluted water environments, probably due to the presence of organic matter or solid particles. Alvarez et al . ( 2000 ) reported that the inactivation of bacteriophage MS2 and poliovirus in pre-fi ltered ground water was faster than in raw ground water.…”
Section: Persistence In Aquatic Environmentsmentioning
confidence: 99%